2020
DOI: 10.21203/rs.3.rs-78041/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Tree Species Diversity and Stand Structure on Carbon Stocks of Homestead Forests in Maheshkhali Island, Southern Bangladesh

Abstract: BackgroundThis study aimed to estimate the carbon (C) stocks in homestead forest ecosystems (trees, litterfall, and soil) of Maheshkhali Island in Bangladesh and how tree species diversity and stand structural variation affected these C stocks. We randomly surveyed a total of 239 homestead forests proportionately allocating in hillside (67), beachside (69), and inland (103) in 2019 for measuring woody plants and sampling litterfall and C in soil at 0-30 cm depth. Tree (above- and below-ground) biomass was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(99 reference statements)
1
4
0
Order By: Relevance
“…From the result obtained, Pinus carribaea had the highest total carbon stock, having a total of 408 sampled trees in the plantation and the dbh ranges from 32cm-108cm, as compared to Nauclea diderrichhi plantation that has a lesser concentration, with a total of 108 sampled trees and dbh range from 18cm-204cm. This agrees to the finding of [27] who stated that species coverage contributes to the total carbon stock were more in line with their relative abundance [28]. From the result obtained, it is observed that Carbon sequestration capacity varies from species, age, tree sizes in terms of DBH and height, as well as the stand growth of each of the plantations under study.…”
Section: Discussionsupporting
confidence: 90%
“…From the result obtained, Pinus carribaea had the highest total carbon stock, having a total of 408 sampled trees in the plantation and the dbh ranges from 32cm-108cm, as compared to Nauclea diderrichhi plantation that has a lesser concentration, with a total of 108 sampled trees and dbh range from 18cm-204cm. This agrees to the finding of [27] who stated that species coverage contributes to the total carbon stock were more in line with their relative abundance [28]. From the result obtained, it is observed that Carbon sequestration capacity varies from species, age, tree sizes in terms of DBH and height, as well as the stand growth of each of the plantations under study.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have found that combining different families of native and exotic trees improves carbon sequestration performance [22,37,38]. Mixing different species of trees had more profound results in carbon storage [39,40].…”
Section: Carbon Sequestration By Treesmentioning
confidence: 99%
“…High species diversity is a necessary condition for maintaining the forest multifunctionality and increasing most of its functions (Sanaei et al, 2021) such as promoting productivity in forests (Morin et al, 2011), correlating with carbon stocks (Baul et al, 2021;Sintayehu et al, 2020;Wakhidah et al, 2020), potentially increasing the resilience of green plantations to disturbances and stresses, including drought (Palandrani et al, 2020), and reducing damage caused by insects and pathogens (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%